استخدام نماذج بيانات البانل لدراسة محددات تنمية رأس المال البشري في دول المغرب العربي للفترة (2000-2018) - بوصبع, سهام (جامعة الوادي - University of Eloued, 2021)
The study aimed to measure and analyze the determinants of human capital development in the Arab Maghreb Countries using the Panel data models, and annual data during the period (2000- 2018), wich was processed though the statistical program Eviews11. The results of the study showed That the Fixed Effects Model is the appropriate model for the study, meaning that the difference between countries is due to the Intercept. The results of the same model showed that there is a positive and significant impact of economic growth and the number of Internet subscribers on human capital development, while the impact was Negative and significant for government spending on health, and negative and insignificant for government spending on education
Using Panel Data Model to study the determinants of Human Capital Development in Arab Maghreb Countries during the period (2000-2018)
مقال
Keywords: تنمية رأس المال البشري؛ ; نماذج بيانات البانل؛ ; دول المغرب العربي; Human Capital Development; Arab Maghreb Countries; Panel Data Model